Review of the text by Zulay C. Díaz Montiel. Raúl Fornet - Betancourt: Intersubjectivity, Dialogue and Intercultural Ethics. An interpretation from Latin American philosophy. Brazil: Nova Petró-polis: Nova Harmonia / Universidad del Zulia, 2017. Pp. 9 - Capera Figueroa, José Javier (2021)
Revisión del texto de Zulay C. Díaz Montiel. Raúl Fornet - Betancourt: intersubjetividad, diálogo y ética intercultural.